2007
DOI: 10.1177/0165025407073930
|View full text |Cite
|
Sign up to set email alerts
|

Children's perceptions of group variability as a function of status

Abstract: Two studies focused on perceived ingroup and outgroup variability in children as a function of status. In the first study, 7- and 9-year-old White and Black children distributed White and Black faces along the levels of several dimensions. White children perceived more ingroup than outgroup variability, whereas Black children perceived more outgroup than ingroup variability. In addition, White children favored their ingroup, whereas Black children did not. In a second study, 7- and 9-year-old boys and girls di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
0
15
0
1
Order By: Relevance
“…Prior research on the perception of group variability as a function of group status has indeed documented a minority homogenization bias. It has been found, for example, that both majority (e.g., White) and minority (e.g., Black) children perceived faces of minority children in a more homogenizing way than faces of in‐group members (Guinote et al., ). Similarly, Birnbaum et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research on the perception of group variability as a function of group status has indeed documented a minority homogenization bias. It has been found, for example, that both majority (e.g., White) and minority (e.g., Black) children perceived faces of minority children in a more homogenizing way than faces of in‐group members (Guinote et al., ). Similarly, Birnbaum et al.…”
Section: Discussionmentioning
confidence: 99%
“…Guinote et al. () found that White children perceived the out‐group in a more homogeneous way than the in‐group. In contrast, Black children perceived the out‐group in a more variable way than the in‐group, that is, the opposite of an out‐group homogeneity bias.…”
mentioning
confidence: 99%
“…Many studies have also shown higher levels of in-group preference among members of ethnic majority groups (e.g., Asher & Allen, 1969;Bettencourt & Bartholow, 1998;Ellemers, Doosje, van Knippenberg, & Wilke, 1992), especially high-status majority groups, and that minority-group members often favour majority-group members, especially when the majority has higher status (Aboud, 1988;Guinote, Mauro, Pereira, & Monteiro, 2007;Otten, Mummendey, & Blanz, 1996;.…”
Section: Social Outcomes As a Function Of In-group Preference And/or mentioning
confidence: 99%
“…For example, McLoughlin and Over (2017) found that 5-and 6-year-olds used more mental state terms when describing ingroup members than outgroup members and that 6-year-olds used a greater diversity of mental state terms when describing ingroup members than outgroup members. Further evidence suggests that children as young as 5 are better at recognizing variability in the physical characteristics, interests, and personality of members of their own racial group than members of a different group-an effect that tends to be strongest among children who belong to majority groups (Guinote, Mouro, Pereira, & Monteiro, 2007;Simon & Brown, 1987).…”
Section: Individuation and Intergroup Attitudesmentioning
confidence: 99%